2003
DOI: 10.1210/rp.58.1.199
|View full text |Cite
|
Sign up to set email alerts
|

Overlapping but Distinct Profiles of Gene Expression Elicited by Glucocorticoids and Progestins

Abstract: Glucocorticoids and progestins bind to receptors that share many structural and functional similarities, including virtually identical DNA recognition specificity. Nonetheless, the two hormones mediate very distinct biological functions. For example, progestins are associated with the incidence and progression of breast cancer, whereas glucocorticoids are growth suppressive in mammary cancer cells. To understand the mechanisms that engender biological specificity, we have employed two systematic approaches to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 65 publications
0
23
1
Order By: Relevance
“…To explore the underlying molecular mechanisms of GC-induced breast epithelial cell survival, we performed a genome-wide screen using high-density oligonucleotide microarrays to identify GC-regulated genes. Interestingly, the gene expression changes we observed in MCF10A-Myc cells differ significantly from those previously identified both in lymphocytes (32) and in the breast cancer tumor cell line T47D-GR (33). A possible explanation for these results is the differential expression of GR coactivator and corepressors in different cell types, a mechanism that has been proposed to explain the opposite effects of tamoxifen on mammary versus endometrial tissue (34).…”
Section: Discussioncontrasting
confidence: 59%
“…To explore the underlying molecular mechanisms of GC-induced breast epithelial cell survival, we performed a genome-wide screen using high-density oligonucleotide microarrays to identify GC-regulated genes. Interestingly, the gene expression changes we observed in MCF10A-Myc cells differ significantly from those previously identified both in lymphocytes (32) and in the breast cancer tumor cell line T47D-GR (33). A possible explanation for these results is the differential expression of GR coactivator and corepressors in different cell types, a mechanism that has been proposed to explain the opposite effects of tamoxifen on mammary versus endometrial tissue (34).…”
Section: Discussioncontrasting
confidence: 59%
“…However, P and MPA may not affect GR in the same manner as glucocorticoids do. Indeed, activation of GR via progestins versus glucocorticoids results in differential gene transcription (Wan and Nordeen, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…NAM is a reaction intermediate of SIRT1 deacetylation activity that feeds back to inhibit the deacetylation activity of SIRT1 (4,17). The effect of NAM on PR-mediated transcription was determined by using T47D/2963.1 (2963.1) human breast cancer cells that endogenously express PR (45) that were treated with or without NAM for 30 min, followed by treatment with synthetic progesterone R5020 or vehicle (EtOH) for 4 h. RT-PCRs were performed from isolated RNA, and the expression levels of known PR-regulated genes CEBP/␤, EZF and SGK (53,62) were analyzed by real-time PCR. The RT-PCR analysis revealed that NAM inhibits hormone-dependent activation of PR-regulated genes in a dosedependent manner (Fig.…”
Section: Rna Isolation and Reverse Transcription-pcr (Rt-pcr)mentioning
confidence: 99%